The Yoruba Muslims and the Credence in Reincarnation: An Orthodox Intrusion - Ismail Adaramola Abdul Azeez; Amidu Adinoyi Jimoh (International Journal of Integrative Sciences, 2023)
Everybody knows that death is the unescapable end of man. What waves the mind of many, consciously or otherwise, is the question of what happens to man when he breaths his last breath.  While some are of the opinion that after death comes judgment; a determent of whether one goes to eternal blissful domains, or into everlasting tenant; depending on whether he had lived piously or otherwise, while on earth. Another school of thought opines that the soul of the dead will reincarnate by taking abode in a new physical body, born as a new baby and live another normal life, whereby he/she has the opportunity to correct his/her wrong actions in the previous incarnation. While some are of the opinion that when the soul has gathered wisdom, knowledge and understanding through several incarnations, it becomes one with the creator; others believe that reincarnation is a continuous process without neither beginning nor an ending. The Yoruba of South-Western Nigeria, like most other Africans, believes that humans reincarnate in order to re-choose their destiny and fulfill their life ambitions which they had no chance to achieve in a previous incarnation. An examination of some Yoruba traditional songs about death and what follows, show that they believe in 'a day of reckoning' and the continuum of the life cycle. Reincarnation, generally speaking, is always thought of, and discussed as a religious phenomenon, most probably because it borders on the super-natural; an issue to which only God; the creative force, has the totally correct answer